Banks in Crisis : the Legal Response - Campbell, Andrew; Cartwright, Peter (Routledge Revivals, 2017)
"This title was first published in 2002: A detailed and critical analysis of the various legal problems that arise when banks are in serious financial difficulty, Banks in Crisis offers an invaluable, international perspective on the concept and causes of bank failure. It takes an authoritative and much-needed look at a number of key issues including: - Effective bank regulation as an instrument in the possible prevention of banking crises, with particular reference to the role of the Financial Services Authority in the UK, and the impact of the Financial Services and Markets Act 2000 - The role of the Bank of England in the new regulatory landscape, with particular reference to its function as lender of last resort - The legal controls on those involved in the management of banks - Insolvency procedures and bank liquidation - The use of depositor protection schemes. By drawing conclusions and weighing up the methods available to promote stability, prevent failure and promote rescues where appropriate, Banks in Crisis is an essential read and a welcome addition to this crucial area of research."--Provided by publisher.